Music performance anxiety: Priority targets in prevention and intervention - Martins, M. (2024)
Background: Music Performance Anxiety (MPA) is a major setback for musicians with diverse backgrounds and expertise. MPA can be managed with adequate strategies, and success will improve if information and professional help is widely available and if musicians are willing to seek such help. Research on MPA has focused on the correlates (potential causes) of MPA, but results are scattered across studies. Also, the correlates of musicians’ willingness to mitigate MPA remain underexplored. Method: To address the referred gaps, we inspected eleven sociodemographic and music-related predictors of MPA in a single sample and investigated potential correlates of musicians’ coping strategies and openness to professional help. Results: Results from 184 Portuguese and Brazilian musicians pointed to age, sex, and discrepancies between real and ideal self as a musician as the most relevant predictors of MPA. Regarding coping strategies, we found that females, Portuguese, classical performers and those exposed to higher levels of external judgment resort more than males, Brazilians, non-classical and low-exposure musicians to physiology-related methods. Openness to professional help was lower in Portuguese, classical and high-exposure musicians, and in low-MPA performers. Conclusion: These findings contribute to better identifying individuals at risk of developing and perpetuating MPA, thus allowing more efficient awareness campaigns and intervention programs.